Melanoma cell necrosis facilitates transfer of specific sets of antigens onto MHC class II molecules of dendritic cells - Röhn, Till Alexander; Schadendorf, Dirk; Sun, Yuansheng; Nguyen, Xuan-Duc (European journal of immunology, 2005)
Vaccine strategies that target dendritic cells (DC) in order to elicit immunity against tumors are the subject of intense research. For the induction and maintenance of anti-tumor immunity, CD4+ helper T cells are often required, which need to see appropriate MHC class II-peptide complexes on DC. So far, it remained widely unclear what type of tumor cells can feed the MHC class II processing pathway of DC with what type of antigens. Here, we report that peptide loading onto MHC class II molecules of myeloid DC is facilitated by melanoma cells undergoing necrotic rather than apoptotic cell death. Importantly, the set of MHC class II-associated peptides induced by necrotic tumor cells differed from those found upon engagement of apoptotic tumor cells. This may be due to the fact that only necrotic cells liberated heat shock proteins, which bind tumor-derived peptides and thereby may promote processing by DC. The potential of DC to activate T cells was kinetically controlled through their antigen receptivity: CD4+ T cells were easily stimulated upon encountering antigen early in DC maturation, whereas antigen capture at later maturation stages favored activation of CD8+ T cells. These findings may aid in designing future vaccination strategies and in identifying novel tumor-specific helper T cell antigens.